The construction of protest how newspapers frame anti-Arroyo protests - Baguyo, Lewelyn Zambrano (2009.)
"This study on frames and framing of protests aims to identify and characterize dominant frames used by journalists in narrating anti-Arroyo protests. Frames are the organizing ideas of a news story that are emphasized through framing devices. Framing devices are comprised of lexical choices of journalists and journalism routines that construct depictions of protests and protesters. The study seeks to establish the prevalence of characteristics of "protest paradigm", such as use of sources, invocation of public opinion, delegitimization and marginalization techniques as framing devices. The study also explores differences and similarities in framing among broadsheet and tabloid newspapers. Using an inductive approach, frames are identified by probing how key words and phrases convey specific interpretations of protest and depict identities of protest groups. This study found that news stories commonly frame protests as disruptions of social order while depicting protesters as deviant. This study aldo found that descriptors, use of sources, delegitimization and marginalization techniques are the most common framing devices used by journalists. The findings of this study show that there are variations in framing of protest among newspaper media."
Thesis (M.A. Communication Research)--University of the Philippines, Diliman.
Vita.
Keywords: Government and the press -- Philippines; Journalism -- Political aspects -- Philippines